Developing Precisely Defined Drug‐Loaded Nanoparticles by Ring‐Opening Polymerization of a Paclitaxel Prodrug. Issue 15 (25th April 2016) - Liu, Jinyao; Pang, Yan; Bhattacharyya, Jayanta; Liu, Wenge; Weitzhandler, Isaac; Li, Xinghai; Chilkoti, Ashutosh
Abstract : Nanoparticles with high paclitaxel (PTX) loading and low systemic toxicity are prepared in scalable and versatile manner via one‐step ring‐opening polymerization of a prodrug monomer consisting of PTX that is appended to a cyclic carbonate through a hydrolysable ester linker. Initiating this monomer from a hydrophilic macroinitiator results in an amphiphilic diblock copolymer that spontaneously self‐assembles into well‐defined nanoparticles with tunable size.